Changes in food and drink purchasing behaviour in England during the first 3 months of the COVID-19 pandemic: an interrupted time series analysis - Alexandra Kalbus; Laura Cornelsen; Andrea Ballatore; Steven Cummins (Public Health Nutrition)
Abstract